Metal-sulfide-decorated ZnO/Si nano-heterostructure arrays with enhanced photoelectrochemical performance - Yadian, Boluo (2017)
The present work reports an effective approach to fabricate highly ordered arrays of ZnO/Si heterostructures decorated with metal sulfides (i.e. ZnS and Ag2S). These metal-sulfide-coated ZnO/Si heterostructure arrays are then used as a photoanode in the photoelectrochemical water splitting system. The significant enhancement of ZnO/Si heterostructure arrays in photo-current density and on/off ratio is demonstrated after they are coated with metal sulfides. These metal-sulfide-coated ZnO/Si heterostructure arrays are a promising building block for the fabrication of optoelectronic devices such as photoelectrochemical cells.